Clinical features, angio-architectural phenotypes, and treatment strategy of foramen magnum dural arteriovenous fistulas: a retrospective case series study - Xiao, Zhipeng; Gao, Weizhen; Zhou, Hongyu; Zhang, Xiaohua; Dai, Jiong; Wan, Jieqing; Guo, Liemei (Frontiers in Neurology, 2023)
Background The rarity and angio-architecture complexity of foramen magnum dural arteriovenous fistulas (DAVFs) make the treatment difficult and controversial. We aimed to describe their clinical features, angio-architectural phenotypes and treatments, through a case series study. Methods We first retrospectively studied cases of foramen magnum DAVFs treated in our Cerebrovascular Center, and then reviewed the published cases on Pubmed. The clinical characteristics, angio-architecture and treatments were analyzed. Results 55 patients (50 males and 5 females) were diagnosed as foramen magnum DAVFs, with a mean age at 52.8 years. Most patients presented with SAH (21/55) or myelopathy (30/55), depending on the venous drainage pattern. 21 DAVFs were supplied by only the vertebral artery (VA), 3 by only the occipital artery (OA), 3 by only the ascending pharyngeal artery (APA), and the other 28 DAVFs by two or three of these feeding arteries. Most cases (30/55) were treated with only endovascular embolization, 18 cases (18/55) with only surgical disconnection, 5 cases (5/55) with combined therapy, and 2 cases rejected treatment. Complete obliteration of the fistula was achieved in most patients (50/55). In addition, we have treated 2 cases of foramen magnum DAVFs in Hybrid Angio-Surgical Suite (HASS) with good outcomes. Conclusions Foramen magnum DAVFs are rare, and their angio-architectural features are complicated. The treatment option (microsurgical disconnection or endovascular embolization) should be weighed carefully, and combined therapy in HASS could be a more feasible and less invasive treatment option.